Pd@Al2O3-Catalyzed Hydrogenation of Allylbenzene to Propylbenzene in Methanol and Aqueous Micellar Solutions (2015)
The palladium on alumina (Pd@Al2O3)-catalyzed hydrogenation of allylbenzene to propylbenzene was studied in methanol and aqueous micellar solutions of sodium dodecyl sulfate (SDS), decyltrimethylammonium bromide (DTAB), and t-octylphenoxypolyethoxyethanol (TX-100). Over Pd@Al2O3, propylbenzene was obtained via direct hydrogenation of allylbenzene and isomerization to ß-methylstyrene which was hydrogenated afterwards. In aqueous micellar solutions, the reaction was faster than in pure water, but slower than in methanol due to lower hydrogen solubility. In the H2O/SDS system, a higher activation energy was obtained than in methanol. For the investigated surfactants, the initial reaction rate in the micellar systems decreased in the order SDS >TX-100 >DTAB. © 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.